Primary adenocarcinoma of the seminal vesicle - Safae Terrisse; Maria Eugenia Comblor; Jérôme Vérine; Hélène Gauthier; Pierre Mongiat-Artus; Stéphane Culine (Rare Tumors, 2017)
Primary adenocarcinoma of the seminal vesicle is a rare condition with only about 60 cases described in the literature. The unusual characteristics of this disease makes diagnosis difficult and treatment strategies differ as there are no specific guidelines available. This report presents a case of adenocarcinoma of the seminal vesicle with lung metastases in which surgical and chemotherapeutic treatments have been carried out. The MVAC dose dense regimen following local resection seems effective in this scenario and may be used in the treatment of this disease.